E-Voting: Kebutuhan vs. Kesiapan (Menyongsong) E-Demokrasi - Hardjaloka, Loura; Simarmata, Varida Megawati (Jurnal Konstitusi, 2011)
Along with the success of e-voting in the election of leaders at the village in Jembrana District, Bali Province, the Chief Electoral Hamlet (Kelihan Banjar Dinas) in the Village Yehembang, Pohsanten Village, District and Village Mendoyo Perancak, Jembrana district by using the e-ID card, opening new opportunities for Indonesia to use these methods in the upcoming election. However, by retaining Article 88 of Law Number 32 Year 2004 regarding Regional Government provides the opportunity for areas not yet ready for e-voting to keep using conventional mencontreng election or vote.